Dewey Decimal Classification development during the COVID-19 pandemic - Kyrios, Alex (Access: An International Journal of Nepal Library Association, 2022)
This article provides an overview of the revision process for the Dewey Decimal Classification (DDC), with an emphasis on the user advisory group Editorial Policy Committee (EPC), and recent efforts to prioritize community-driven changes. It details how these processes have been affected by the COVID-19 pandemic, including innovations, challenges, and lessons for the future. It also includes three example cases of revisions that happened mostly or entirely during pandemic-era remote work.